PENGARUH PENGETAHUAN, KUALITAS LAYANAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Daniswara, Endra Rasendriya; Dian Anita Nuswantara (Journal of Innovation Research and Knowledge, 2025)
The rapid development of e-commerce has provided new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in Surabaya City to expand their market reach and enhance competitiveness. However, this growth also presents challenges in terms of tax compliance, as many MSMEs lack a thorough understanding of their tax obligations, which can lead to non-compliance and potential sanctions. This study aims to explore the influence of tax knowledge, service quality, and tax sanctions on the tax compliance of e-commerce MSMEs. The research employs a quantitative approach with a convenience sampling technique, involving 346 respondents who are e-commerce taxpayers with a registered taxpayer identification number. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test the proposed hypotheses. The results indicate that tax knowledge, service quality, and tax sanctions significantly influence tax compliance among MSMEs. Tax knowledge enhances compliance by reducing the likelihood of administrative errors, while high-quality tax services, including responsive and accessible support, further encourage compliance by facilitating the tax process. Additionally, consistent and transparent enforcement of tax sanctions deters non-compliance and upholds the integrity of the tax system. The findings suggest that to improve tax compliance, authorities should prioritize tax education, enhance service quality through digitalization, and implement firm but fair sanctions.